2006
DOI: 10.1208/pt070124
|View full text |Cite
|
Sign up to set email alerts
|

Use of hydrophilic natural gums in formulation of sustained-release matrix tablets of tramadol hydrochloride

Abstract: The objective of this work was to develop matrix sustainedrelease tablets of highly water-soluble tramadol HCl using natural gums (xanthan [X gum] and guar [G gum]) as costeffective, nontoxic, easily available, and suitable hydrophilic matrix systems compared with the extensively investigated hydrophilic matrices (ie, hydroxypropyl methylcellulose [HPMC]/carboxymethyl cellulose [CMC] with respect to in vitro drug release rate) and hydration rate of the polymers. Matrix tablets of tramadol (dose 100 mg) were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 38 publications
5
63
0
Order By: Relevance
“…For tablets from the PG3 batch, first-order kinetics are evident with no constant term. Initial drug release can be rapid because water uptake is higher and faster with guar gum than with other natural gums, such as xanthan gum (23). Similar initial rapid drug release has been reported with soluble drugs salbutamol sulfate (55) and tramadol HCl (23), although the initial release of diltiazem HCl could be controlled (20).…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…For tablets from the PG3 batch, first-order kinetics are evident with no constant term. Initial drug release can be rapid because water uptake is higher and faster with guar gum than with other natural gums, such as xanthan gum (23). Similar initial rapid drug release has been reported with soluble drugs salbutamol sulfate (55) and tramadol HCl (23), although the initial release of diltiazem HCl could be controlled (20).…”
Section: Resultsmentioning
confidence: 63%
“…Although it is considered a nongelling gum, it generates a viscous medium due to its tenuous associations (16). Although it is highly swellable, it slows drug release in sustained release formulations (11,23).…”
Section: Introductionmentioning
confidence: 99%
“…The result was unexpected since higher amount of drug release is supported by smaller MDT. 25 The observed deviation in MDT values could possibly related to hydration and erosion of polymeric matrix. The drug release in xanthan gum matrix tablets was slower in comparison to HPMC matrix up to 4 h of dissolution studies.…”
Section: Model Dependent and Independent Analysismentioning
confidence: 99%
“…Similarly, drug release from the matrix was also affected by the concentration of gum olibanum in the matrix. Varshosaz et al 25 observed that inclusion of xanthan gum and guar gum has significantly modified tramadol release from HPMC matrix tablets. When two or more polymers are used in a matrix, if they form a semi-or complete interpenetrating network, it form a rigid matrix resulting in slower drug release.…”
Section: Model Dependent and Independent Analysismentioning
confidence: 99%
“…Galactomannans are also essential hydrophilic materials with a variety of properties, such as being nontoxic, biodegradable, inexpensive, and readily available. The potential of galactomannans from different sources to be applied as release-controlling agents has been extensively investigated (Varshosaz et al 2006).…”
Section: Introductionmentioning
confidence: 99%